2021
DOI: 10.1177/15593258211058341
|View full text |Cite
|
Sign up to set email alerts
|

Smoke Screen to Distract From Flawed Science: A Response to Côté et al. Over Criticisms to Their Deficient ‘Rapid Review’ on Chiropractic X-Ray Utility

Abstract: Côté et al. attempted to review the clinical utility of X-ray within chiropractic (1910( -Nov. 25, 2019. 1 After reviewing only 9 articles, the most recent dated by 15 years, they concluded "Given the inherent risks of ionizing radiation, we recommend that chiropractors do not use radiographs for the routine and repeat evaluation of the structure and function of the spine." 1 We recently showed dozens of chiropractic studies that were missed according to their own very strict inclusion/ exclusion criteria, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In view of its evident lack of biological plausibility and the accumulated evidence to the contrary, the motives behind continuing to base radiation protection of the LNT hypothesis are not easily discernible but they may include ethical improbity, dogmatic policy assumptions, institutional inertia and comfort, the love of money and power, conventional respect, and even corruption and fraud (reviewed in Refs. 6,9,11,76,77). Apart from the scientists, policy makers and advisory bodies, the blame is certainly shared by the radiation protection community which has been recently downrightly accused of ‘choosing not to speak up against the excessiveness that has come to define the public conversation surrounding radiation’ , 78 this decision assuring continued radiophobia.…”
Section: Introductionmentioning
confidence: 99%
“…In view of its evident lack of biological plausibility and the accumulated evidence to the contrary, the motives behind continuing to base radiation protection of the LNT hypothesis are not easily discernible but they may include ethical improbity, dogmatic policy assumptions, institutional inertia and comfort, the love of money and power, conventional respect, and even corruption and fraud (reviewed in Refs. 6,9,11,76,77). Apart from the scientists, policy makers and advisory bodies, the blame is certainly shared by the radiation protection community which has been recently downrightly accused of ‘choosing not to speak up against the excessiveness that has come to define the public conversation surrounding radiation’ , 78 this decision assuring continued radiophobia.…”
Section: Introductionmentioning
confidence: 99%
“…In the manual therapies literature, there has been debate as to the usefulness of radiographic screening of the sagittal spinal curves 12 , 13 , 14 , 15 , 16 , 17 ) . For instance, Christensen and Hartvigsen concluded that “Evidence from epidemiological studies does not support an association between sagittal spinal curves and health including spinal pain,” even though the authors found several health conditions having statistically significant odds ratios in the presence of altered spine alignment, including death, they claimed the relationships are ‘unlikely to be causal’ 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins et al 14 ) ; Corso et al. 15 ) ), but fail to accurately interpret the very studies that they referenced that actually provide high-level, supportive evidence and rationale for utilizing spine re-alignment treatments (and therefore X-rays) 16 , 17 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As various fields in medicine increasingly take advantage of newly developed diagnostic technologies, which include some form of low dose radiation exposure, reticence within the public to accept these new diagnostics and even established diagnostics such as X rays, CT scans and mammograms remains a significant challenge in medicine ( 9799 ). There is an intrinsic and disproportionate fear of radiation because it is a member of a class of agents known as “dreaded risk” agents.…”
Section: Introductionmentioning
confidence: 99%